MUTUAL FUNDS PERFORMANCE EVALUATION BASED ON SELECTIVITY AND MARKET TIMING - Murhadi, Werner R. (IQTISHODUNA, 2011)
This paper is an empirical evaluation of the performance of mutual fund managers in terms of â€œmarket timingâ€ and â€œselectivityâ€, within the framework suggested by Treynor and Mazuy (1966) and Henriksson and Merton (1981). The relevant data set is a balanced panel of 55 (fifty five) mutual funds, over a 17 (seventeen)-month period began from February 2008 until June 2009. The result found that only 4 (four) mutual funds demonstrated a good performance in market timing and 4 (four) mutual funds showed a good performance in stock selection. Both methods have a good indicator to reflect mutual funds performance.